Diabetes (db/db) mutation-induced endometrial epithelial lipoapoptosis: Ultrastructural and cytochemical analysis of reproductive tract atrophy - Garris David R (BMC, 2005)
Abstract Background The diabetes (db/db) mutation in C57BL/KsJ mice promotes a progressive cytolipidemia within the endometrial epithelial (EE) layer of the female reproductive tract which results in premature cellular and organ atrophy. The current studies focus on the ultrastructural and cytochemical changes which promote nuclear apoptosis and cytostructural disruption following the expression of endometrial hypercytolipidemia which promotes diabetes-associated organoinvolution and manifest infertility. Methods Control (normal:+/+) and diabetes (db/db) genotype groups were prepared for high resolution light microscopic analysis of cytolipidemia and nuclear apoptosis (TUNEL-labeled 3'-DNA fragmentation) indices and compared to the transmission electron (TEM) microscopic analysis of endometrial tissue samples collected from 8-16 week-old groups. Results Compared to controls, db/db mutation expression induced a dramatic increase in EE cytolipid vacuole volume and density within the epithelial endometrial layer. TEM analysis revealed that cytolipid vacuole accumulations initially aggregated at the baso-polar regions of UEE cells in response to the systemic hyperglycemic/hypertriglyceridemic conditions which characterized the (db/db) groups. Progressive cytoplasmic movement of the lipid pools into perinuclear compartments of affected EE cells induced nuclear isolation from organelles that were displaced towards peripheral cytoplasmic compartments. Cytochemical analysis of lipid vacuole accumulations indicated attraction towards, and incorporation within, the nuclear envelope of hyperlipidemic cells. Co-localization of nuclear apoptotic 3'-DNA fragments within identified hyperlipidemic EE cells was coincident with the cytochemical and ultrastructural identification of lipid penetration through the nuclear envelope in db/db mutants. Conclusion These results are the first cytochemical indication that the metabolic disturbances in db/db mutants which promote hypercytolipidemia are coincident with lipoapoptosis-induced nuclear dissolution, as denoted by DNA fragmentation analysis. The lipidemia-induced alterations in intracellular organelle and nuclear architectures suggests that the metabolic disturbances in glucose and lipid metabolic cascades in diabetes (db/db) mutants disrupts cytointegrity, culminating in nuclear disregulation (as indicated by lipoapoptosis) and eventual premature reproductive tract organoinvolution and resultant, manifest, reproductive sterility.